Survey Of Sports Injuries In Young Football Athletes In Football Competitions - M. Akabr Husein Allsabah; Sugito Sugito (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Sports injuries are a big problem for coaching young athletes to prepare to become professional players. Therefore, it is necessary to know the incidence of injury and the type of injury in sports or football matches so that coaches and players can anticipate injury events. The purpose of this study was to determine the incidence of injuries and types of injuries of young football players in a youth football coaching competition. This research method is a survey with an interview approach and filling out a questionnaire about sports injuries after the game, the questionnaire has been validated by validators according to their fields. The subject of this research is 360 football players who participated in the Bola Kediri Cup 2022 event. The results of this study were that of the 360 players who participated in the Bola Kediri Cup 2022 match, 121 or 33.6% of players did not experience injuries, while 239 or 66.4% of players suffered injuries. Meanwhile, the type of injury that most affects players is muscle cramps 79 or 33.1%. From the results of this study, players and coaches can find out and minimize the incidence of injuries in football matches. Minimizing these injuries can be done by preparing players in shape so that players are ready during the game.